2009
DOI: 10.1128/iai.00824-09
|View full text |Cite
|
Sign up to set email alerts
|

Role for theBurkholderia pseudomalleiCapsular Polysaccharide Encoded by thewcbOperon in Acute Disseminated Melioidosis

Abstract: The capsular polysaccharide of Burkholderia pseudomallei is an essential virulence determinant that is required for protection from host serum cidal activity and opsonophagocytosis. In this study, the immune response directed against a B. pseudomallei capsule mutant (JW270) was investigated in an acute respiratory murine model. JW270 was significantly attenuated in this model (ϳ2 logs) to levels resembling those of avirulent Burkholderia thailandensis. At lethal doses, JW270 colonized the lung, liver, and sple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
53
2
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 45 publications
6
53
2
1
Order By: Relevance
“…The genes retained by B. mallei have an average identity of 99% at the nucleotide level with their B. pseudomallei orthologs, and of those, 650 have been proposed to form a core virulome based on comparative genomic analysis and sequence similarity to known virulence factors (28). Consistent with these in silico predictions, many virulome genes have been shown to specify key determinants in the pathogenesis of glanders and melioidosis, including lipopolysaccharide (LPS) (29,30), type 3 and type 6 secretion systems (31)(32)(33)(34)(35)(36)(37), and capsule (38)(39)(40)(41). In addition to their high level of genomic relatedness, the clinical and pathological manifestations of disease caused by B. mallei and B. pseudomallei are markedly similar.…”
supporting
confidence: 50%
“…The genes retained by B. mallei have an average identity of 99% at the nucleotide level with their B. pseudomallei orthologs, and of those, 650 have been proposed to form a core virulome based on comparative genomic analysis and sequence similarity to known virulence factors (28). Consistent with these in silico predictions, many virulome genes have been shown to specify key determinants in the pathogenesis of glanders and melioidosis, including lipopolysaccharide (LPS) (29,30), type 3 and type 6 secretion systems (31)(32)(33)(34)(35)(36)(37), and capsule (38)(39)(40)(41). In addition to their high level of genomic relatedness, the clinical and pathological manifestations of disease caused by B. mallei and B. pseudomallei are markedly similar.…”
supporting
confidence: 50%
“…Addi-tionally, the Bsa T3SS influences the virulence of Burkholderia mallei (33). A polysaccharide capsule encoded by the wcb operon also plays a pivotal role in the pathogenesis of murine melioidosis (37). It has previously been reported that a polysaccharide capsule protects Streptococcus pneumoniae against entrapment in NETs (38); however, the role of capsule and of the Bsa T3SS in interactions with human PMN has received little study.…”
mentioning
confidence: 99%
“…infection; 15,16 acapsular mutants are strongly attenuated; 14,17,18 and the biosynthetic genes are absent in related, less pathogenic species. 14 In addition to providing a general defence against immune challenge, B.…”
mentioning
confidence: 99%